Impostors Dare to Compare: Associations Between the Impostor Phenomenon, Gender Typing, and Social Comparison Orientation in University Students - Fassl, Flora; Yanagida, Takuya; Kollmayer, Marlene (Frontiers in Psychology, 2020)
Entering university is often associated with new surroundings and challenges, which can cause distress and might result in poor mental health. A phenomenon that was shown to be linked to low self-esteem, higher stress-levels, anxiety, and depression in university students is the impostor phenomenon. Impostorism is defined as a conviction to be unintelligent despite one’s academic success and was found to be closely associated with psychological femininity in previous studies. Research has also shown that people who experience higher stress-levels, self-doubts, and a low self-esteem tend to engage in social comparison processes more often. Therefore, the present study aimed to explore the relationship between gender typing and impostor feelings and to investigate a possible influence of social comparison orientation on the aforementioned association. For this purpose, 278 university students (73.7% women) completed an online questionnaire. Gender typing was measured using an instrument assessing positive and negative aspects of masculinity and femininity to overcome conceptual limitations of previous studies. For social comparison processes, the general tendency to engage in social comparisons was measured. Of the participants, 8.6% experienced few, 40.3% moderate, 38.5% frequent, and 12.6% intense impostor feelings, which indicates that the impostor phenomenon is highly prevalent in university students. One of the key findings of this study concerns the association between gender typing and the impostor phenomenon. We found a moderate negative relationship between the impostor phenomenon and positive masculinity but no association with negative masculinity. In contrast, impostorism was strongly correlated with negative aspects of femininity but not at all with positive aspects of femininity. The relationship between negative femininity and impostorism was further found to be partially mediated by social comparison orientation. Social comparison orientation, however, was not found to mediate the association between positive masculinity and impostorism. This result indicates that individuals who identify with negative aspects of femininity tend to compare themselves to others more often, which is associated with stronger impostor feelings. Based on the results, we discuss possible interventions to reduce psychological distress among university students.